Synthesis, Structural Characterization and Photocatalytic CO2 Reduction Activity of a New Gd(III) Coordination Polymer with 6-Phenylpyridine-2-carboxylic acid and 4,4’-Bipyridine Ligands - Xi-Shi Tai; Yuan-Fang Wang; Li-Hua Wang; Xi-Hai Yan (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
A new Gd(III) coordination polymer, [Gd(L1)3(H2O)2]∙L2n (1) (HL1 = 6-phenylpyridine-2-carboxylic acid, L2 = 4,4’-bipyridine) was synthesized using 6-phenylpyridine-2-carboxylic acid, 4,4’-bipyridine, NaOH and GdCl3∙6H2O. The structure of Gd(III) coordination polymer has been characterized by IR and X-ray single crystal diffraction. The result of single crystal analysis indicates that fundamental unit of Gd(III) coordination polymer contains one Gd(III) ion, three L1 ligands, two coordinated water molecules and one uncoordinated 4,4’-bipyridine. In 1, the Gd(III) ion is eight-coordinated and surrounded by six O atoms from three L1 ligands and two O atoms from two coordinated water molecules, respectively. The complex 1 exhibits 1D chained structure by the bridging interactions of two carboxyl-oxygen atoms and O−H∙∙∙N hydrogen bonds interactions. The 1D chains are further connected by - stacking interactions to form 3D network architecture. The photocatalytic CO2 reduction activity of complex 1 has also been investigated. The complex 1 exhibits good CO2 reduction activity. With the increase of time, the yield of CO from 18.2 mmol/g in the first hour to 60.3 mmol/g in the third hour. And the CO selectivity has reached 100%. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).